Enhanced vector surveillance to control arbovirus epidemics in Colombia - Sarah Anne J. Guagliardo; Susana Carolina Ardila Roldan; Liliana Santacoloma; Cesar Luna; Juan Manuel Cordovez Alvarez; Juan David Rojas Gacha; Mariana Mansur; Rebecca S. Levine; Audrey Lenhart; Patricia Fuya Oviedo (Pan American Health Organization, 2019)
In the wake of the Zika epidemic, there has been intensified interest in the surveillance and control of the arbovirus vectors Aedes aegypti and Aedes albopictus, yet many existing surveillance systems could benefit from improvements. Vector control programs are often directed by national governments, but are carried out at the local level, resulting in the discounting of spatial heterogeneities in ecology and epidemiology. Furthermore, entomological and epidemiological data are often collected by separate governmental entities, which can slow vector control responses to outbreaks. Colombia has adopted several approaches to address these issues. First, a web-based, georeferenced Aedes surveillance system called SIVIEN AEDES was developed to allow field entomologists to record vector abundance and insecticide resistance data. Second, autocidal gravid oviposition (AGO) traps are deployed as an alternative way to measure vector abundance. Third, data collected by SIVIEN AEDES are used to develop mathematical models predicting Ae. aegypti abundance down to a city block, thus allowing public health authorities to target interventions to specific neighborhoods within cities. Finally, insecticide resistance is monitored through bioassays and molecular testing in 15 high-priority cities, providing a comprehensive basis to inform decisions about insecticide use in different regions. The next step will be to synchronize SIVIEN AEDES data together with epidemiological and climatic data to improve the understanding of the drivers of local variations in arbovirus transmission dynamics. By integrating these surveillance data, health authorities will be better equipped to develop tailored and timely solutions to control and prevent Aedes-borne arbovirus outbreaks.